Narcissus × munozii-alvarezii (Amaryllidaceae): a new hybrid from southern Spain - López-Tirado, Javier (Phytotaxa, 2018)
Daffodils are an attractive group by their striking flowers and scents, therefore very appreciated as ornamental plants. Cultivars are very numerous, leading to more than 27,000 names considering them (Kington 2008). In the wild, the Iberian Peninsula can be recognized as the centre of speciation of Narcissus Linnaeus (1753: 289) (Barra et al. 2011). Consequently, the richest global diversity is found there (Hanks 2002). It is a complex genus that according to diverse authors varies from 25 to 87 species (cf. Webb 1980, Blanchard 1990, Mathew 2002, Zonneveld 2008, Aedo 2013, RHS 2016). Moreover, new species are still described (Escobar García 2018). Some daffodils have been described considering only herbarium vouchers. Nonetheless, it is encouraged to study populations from living specimens by two main reasons: (i) some features such as corona or perigone size—and ratios that include them—cannot be retrieved from exsiccata; and (ii) to study daffodils in the wild allow better understanding of their ecology and phenology (Barra Lázaro et al. 2016). The latter is important to clarify species spatial distribution and their hybrids.